1998
DOI: 10.1007/s005850050684
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study of diurnal, seasonal and solar cycle variations of F-region and topside auroral upflows observed by EISCAT between 1984 and 1996

Abstract: A statistical analysis of F-region and topside auroral ion up¯ow events is presented. The study is based on observations from EISCAT Common Programmes (CP) 1 and 2 made between 1984 and 1996, and Common Programme 7 observations taken between 1990 and 1995. The occurrence frequency of ion up¯ow events (IUEs) is examined over the altitude range 200 to 500 km, using ®eld-aligned observations from CP-1 and CP-2. The study is extended in altitude with vertical measurements from CP-7. Ion up¯ow events were identi®ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 19 publications
5
27
1
Order By: Relevance
“…Ion upflow occurred more frequently near solar minimum than solar maximum, but the upward flux is higher near solar maximum than solar minimum by a factor of about 4. The result is in agreement with a study by Foster et al [1998] who found, also using the EISCAT radar facility and data spanning the first of the two solar cycles in this study, that high upward ion flux, >10 13 m −2 s −1 , occurs more frequently near solar maximum, and high upward ion velocity, >100 m s −1 , occurs more frequently near solar minimum. Regarding the solar activity dependence of outflowing ions, Abe et al [2004] showed that the increase in average H + and O + ion velocities with altitude was steeper at solar minimum than at solar maximum below 4000 km but above 4000 km the steepest increase was at solar maximum.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Ion upflow occurred more frequently near solar minimum than solar maximum, but the upward flux is higher near solar maximum than solar minimum by a factor of about 4. The result is in agreement with a study by Foster et al [1998] who found, also using the EISCAT radar facility and data spanning the first of the two solar cycles in this study, that high upward ion flux, >10 13 m −2 s −1 , occurs more frequently near solar maximum, and high upward ion velocity, >100 m s −1 , occurs more frequently near solar minimum. Regarding the solar activity dependence of outflowing ions, Abe et al [2004] showed that the increase in average H + and O + ion velocities with altitude was steeper at solar minimum than at solar maximum below 4000 km but above 4000 km the steepest increase was at solar maximum.…”
Section: Discussionsupporting
confidence: 93%
“…Upward thermal ion flow in the polar ionosphere is influenced by solar activity, as well as by season and by geomagnetic activity [e.g., Endo et al , 2000; Liu et al , 2001]. Foster et al [1998] have investigated the relation between solar activity and occurrence frequency of ion upflow in the polar ionosphere using the EISCAT data from Tromsø (Invariant latitude of 66.2°). They reported that the upward ion velocity is high during low solar activity and that the upward ion flux is high during high solar activity.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical and case studies of the ion upflow have been made with the European Incoherent Scatter (EISCAT) Kiruna‐Sodankylä‐Tromsø (KST) radar facility located near Tormsø [ Blelly et al , 1992; Wahlund et al , 1992; Keating et al , 1990; Foster et al , 1998; Endo et al , 2000]. The EISCAT KST radar enables us to investigate the characteristics of ion upflow, in particular, in the closed field line region because of its location of the invariant latitude of 66.2°.…”
Section: Introductionmentioning
confidence: 99%
“…The EISCAT radar and satellites have frequently observed FA ion upward flows in the upper ionosphere at high latitudes [ Ogawa et al , 2000, and references therein]. The principal proposed mechanisms for the upflows include convection‐driven frictional ion heating [ Foster et al , 1998], electron temperature enhancement in association with soft particle precipitation [ Rodger et al , 1992; Liu et al , 1995; Caton et al , 1996; Seo et al , 1997], and plasma convection shear‐driven ion instabilities [ Ganguli et al , 1994]. Some results suggest that soft particle precipitation is the predominant energy source driving the upflows in the topside ionosphere [ Liu et al , 1995; Ogawa et al , 2003], while some other results using EISCAT radar data suggest that about 50 percent of the upflows occur during intervals of enhanced ion temperature in the F region [ Foster et al , 1998] and hence the energy source of upflow generation remains ill understood.…”
Section: Introductionmentioning
confidence: 99%
“…The principal proposed mechanisms for the upflows include convection‐driven frictional ion heating [ Foster et al , 1998], electron temperature enhancement in association with soft particle precipitation [ Rodger et al , 1992; Liu et al , 1995; Caton et al , 1996; Seo et al , 1997], and plasma convection shear‐driven ion instabilities [ Ganguli et al , 1994]. Some results suggest that soft particle precipitation is the predominant energy source driving the upflows in the topside ionosphere [ Liu et al , 1995; Ogawa et al , 2003], while some other results using EISCAT radar data suggest that about 50 percent of the upflows occur during intervals of enhanced ion temperature in the F region [ Foster et al , 1998] and hence the energy source of upflow generation remains ill understood. Significant fluxes of heavy ions (O + , N + , NO + , O 2 + , N 2 + ), which are major species below F region, have been observed with spaceborne instruments in the magnetosphere during geomagnetically active intervals [ Shelley et al , 1972; Taylor , 1974; Christon et al , 1994; Petersen et al , 1994; Wilson and Craven , 1999].…”
Section: Introductionmentioning
confidence: 99%